Law Enforcement of Sexual Violence on Social Media: An Islamic Restorative Justice Perspective - Setiyawan, Deni; Hadi, Ismet; Rahmad, Noor; Rizqi, Aditya Maulana; Arifah, Kuni Nasihatun (De Jure: Jurnal Hukum dan Syari'ah, 2025)
Justice for victims of sexual violence on social media is still not fully realised, although positive law has accommodated the restorative justice approach. The existing legal framework is suboptimal, particularly in the aspect of psychological recovery and reconciliation for female victims. This research explores the application of Islamic restorative justice as an alternative approach to dealing with sexual violence in the digital space. The normative research methods used include statutory, comparative, and conceptual approaches. This research analyses the limitations of existing restorative justice practices and the potential of Islamic principles in providing a more holistic solution. The results show that although positive law recognises restorative justice, its application remains weak due to the lack of legal framework, social stigma, the anonymity of perpetrators, and the dominance of retributive punishment. Islamic restorative justice is relevant in the context of sexual violence on social media because it can overcome the existing challenges through the concepts of sulh, diyat, kaffarat, ta’zir punishment, and istighfar. This approach considers not only the legal aspects but also the spiritual, psychological, and social recovery of victims. Strengthening the legal framework that accommodates Islamic restorative justice is crucial in handling cases of sexual violence in the digital era.